Smart Cooling Water Container with IoT - Kamarol Zaman, Mohamad Hazim; Megat Satria Zainuddin, (Progress in Engineering Application and Technology, 2024)
This engineering project centres on the development of an IoT-enabled water-cooling container, innovatively integrating an ESP32 microcontroller with various sensors and actuators for enhanced functionality. Utilizing a temperature sensor and an infrared sensor, the system meticulously monitors the internal environment, ensuring optimal temperature regulation through a Peltier module and maintaining safety by detecting the container's open or closed state. The incorporation of a capacitive touch sensor offers a modern, user- friendly interface, replacing traditional mechanical controls. An OLED display provides real-time feedback on temperature, water level, and battery status, enhancing user interaction. The entire assembly is powered by a rechargeable battery, with efficient power management being a key focus. This project not only demonstrates the practical application of IoT principles in everyday devices but also showcases the seamless integration of hardware and software to create a sophisticated, energy-efficient, and user-centric water-cooling solution.